Answer:
a
Explanation:
Let's use the elimination method on equations 1 and 3 and see what happens:
x + y + 3z = -4
-x - y - 2z = 5
It looks like both the x terms and the y terms cancel out leaving us with the fact that z = 1.
Let's go back to the second equation now and sub in a 1 for z:
2x - z = -3 implies 2x - 1 = -3 and x = -1.
Pick any equation now to sub in the known values to find y. I chose the first one, just because:
x + y + 3z = -4 implies -1 + y + 3(1) = -4 and
-1 + y + 3 = -4 so
y + 2 = -4 and
y = -6
So the solution set is (-1, -6, 1)